The Relationship Between Family Support and the Quality of Life of Patients with Diabetes Mellitus - Rafi, Marni Safitri; Amin, Kurniawan; K, Hairuddin (Bantayang Omni Cendekia, 2024)
Background: In today's modern era, the pattern of people's life structure has undergone changes that trigger people's lifestyles in an unhealthy direction so that it can cause non-communicable diseases, one of which is diabetes mellitus. An increase in the incidence of diabetes mellitus (DM) will have an impact on the physical, psychological, social and economic sufferers. Support from family can help their quality of life because poor family support can affect the quality of life of sufferers which can lead to physical complications. Objective: To determine the relationship between family support and the quality of life of DM patients in the Working Area of Antang Health Center Makassar City. Methods: The research method used was quantitative research with descriptive correlation and cross-sectional approach conducted on 63 samples of DM patients in the Antang Health Center work area obtained by purposive sampling technique, and data collection using validated questionnaires. Results: The results showed good family support as many as 50 people (79.4%) and respondents who had poor family support as many as 13 people (20.6%) while the quality of life was good as many as 48 people (76.2%) and the quality of life was poor as many as 15 people (23.8%). Conclusion: From the results of the study, it can be concluded that there is a relationship between family support and the quality of life of DM patients with p < α values (p = 0.000).